Reticulon‐like proteins in Arabidopsis thaliana: Structural organization and ER localization - Hugues Nziengui; Karim Bouhidel; David Pillon; Christophe Der; Francis Marty; Benoı̂t Schoefs (2007)
Reticulons are proteins that have been found predominantly associated with the endoplasmic reticulum in yeast and mammalian cells. While their functions are still poorly understood, recent findings suggest that they participate in the shaping of the tubular endoplamic reticulum (ER). Although reticulon‐like proteins have been identified in plants, very little is known about their cellular localization and functions. Here, we characterized the reticulon‐like protein family of Arabidopsis thaliana . Three subfamilies can be distinguished on the basis of structural organization and sequence homology. We investigated the subcellular localization of two members of the largest subfamily, i.e. AtRTNLB2 and AtRTNLB4, using fluorescent protein tags. The results demonstrate for the first time that plant reticulon‐like proteins are associated with the ER. Both AtRTNLB proteins are located in the tubular ER but AtRTNLB4 is also found in the lamellar ER cisternae, and in ER tubules in close association with the chloroplasts. Similarity in protein structure and subcellular localization between AtRTNLB2 and mammalian reticulons suggests that they could assume similar basic functions inside the cell.